Electrically gated nanoporous membranes for smart molecular flow control. Issue 44 (6th November 2018) - Kim, Sungho; Ozalp, Ece Isenbike; Darwish, Mohamed; Weldon, Jeffrey A.
Abstract : We report a novel conductive nanoporous membrane platform for a smart drug delivery system, which allows low-power electrically controlled delivery of therapeutic drug molecules via field-effect gating. Abstract : We report a novel conductive nanoporous membrane platform for a smart drug delivery system, which allows low-power electrically controlled delivery of therapeutic drug molecules via field-effect gating. The device was fabricated and tested with two oppositely charged drug molecules for glaucoma treatment. Drug molecules with the same polarity as the channel potential are excluded from the nanochannel by electrostatic repulsion, while molecules with opposite charge are enriched due to electrostatic attraction. Accordingly, the diffusive flow of the charged molecules can be controlled by a single DC gate voltage without the need for any other mechanism. An anodic aluminum oxide (AAO) membrane with 80 nm pore diameter was functionalized by sputtering a chromium (Cr)–gold (Au)–chromium (Cr) stack. The exterior chromium layer was left to oxidize creating the insulation layer for the gate electrode. The resulting pore size was 50 nm in diameter. The +2 V gate voltage increased the transport rate of the ethacrynic acid, which is negatively charged at pH 7.4, by 337% and the −2 V gate voltage decreased the transport rate by 48%. The transport rate of the timolol maleate, which is positively charged in pH 7.4, was decreased by 66% with +2 V gate voltage and increased by 116% with −2 V gate voltage. The transport control was quantified by the on–off ratio (OOR), which is the ratio between the maximum and minimum transport rate. The OOR was altered by surface treatment of the membrane. Removal of the surface charge decreased the OOR of ethacrynic acid from 6.94 to 5.61 and increased the OOR of timolol maleate from 1.36 to 1.99. These measurements were verified by our simulation results. In the simulations, the OOR of ethacrynic acid was decreased from 5.22 to 3.25 and the OOR of timolol maleate was increased from 1.90 to 3.25.